Multi-century tree-ring based reconstruction of the Neuquén River streamflow, northern Patagonia, Argentina - Mundo, Ignacio Alberto (2012)
In most cases, gauged river flow records in southern South America extend for only a few decades, hampering the detection of long-term, decadal to centennial-scale cycles and trends. Long streamflow series can be reconstructed from tree-ring records, offering the opportunity of extending the limited hydrological instrumental data to several centuries. In northern Patagonia, Argentina, the Neuquén River has great importance for local and national socio-economic activities such as hydroelectric power generation, agriculture and tourism. In this study, new and updated tree-ring chronologies from Araucaria araucana and Austrocedrus chilensis are used to reconstruct the October-June mean streamflow for the Neuquén River and place the period of gauged flows (1903-2009), in a long-term, multi-century context. The reconstruction covers the period 1346-2000 AD and was developed from a network of 43 tree-ring chronologies, grouped in composite series, using a nested principal component regression approach. Analyses of the frequency, intensity, and duration of droughts and pluvial events indicate that the 20th century contains some of the driest and wettest annual to decadal-scale events in the last 654 yr, but longer and more severe events were recorded in previous centuries. Blackman-Tukey and singular spectral analyses identified quasiperiodic oscillations from 3.5 to 17.5 yr. A dominant 6.8-yr cycle explains ca. 23.6% of the total variance in the Neuquén River streamflow reconstruction. Correlation analyses showed that discharges of the Neuquén River are related to variations in the Southern Annular Mode (SAM), a measure of air mass exchanges between middle and high latitudes in the Southern Hemisphere. This association is consistent with previous studies that indicate a strong correlation between rainfall in northern Patagonia and SAM variations.